1986
DOI: 10.1002/ajmg.1320230405
|View full text |Cite
|
Sign up to set email alerts
|

Subclavian artery supply disruption sequence: Hypothesis of a vascular etiology for Poland, Klippel‐Feil, and Möbius anomalies

Abstract: A hypothesis is presented to explain the pathogenesis of the Poland, Klippel-Feil, and Möbius anomalies, isolated absence of the pectoralis major with breast hypoplasia, isolated terminal transverse limb defects, and the Sprengel anomaly. We propose that these conditions are the result of an interruption of the early embryonic blood supply in the subclavian arteries, the vertebral arteries and/or their branches, and hypothesize that the occlusions occur at specific locations in these vessels during or around t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
259
0
32

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 564 publications
(301 citation statements)
references
References 41 publications
10
259
0
32
Order By: Relevance
“…of dysmelia) are not caused by genetic defects, but by unspecified "accidents", involving limb amputation, during embryogenesis. We suggest that explanations for unequal frequencies of congenital phantoms for upper and lower as well as for left and right limbs (Table 2) may ultimately be found in the "laws" governing fetal development -such as the slightly earlier development of upper compared to lower limbs (O'Rahilly and Gardner 1975) and the differential vascularization of left and right limb buds (Bouwes Bavinck and Weaver 1986). With respect to this laterality issue, we note the surprisingly low interest by embryologists, teratologists and developmental neuroscientist in this issue and plead for a closer collaboration across the different medical and psychological disciplines.…”
Section: Phantoms Of Congenitally Absent Limbs As Manifestations Of Amentioning
confidence: 95%
“…of dysmelia) are not caused by genetic defects, but by unspecified "accidents", involving limb amputation, during embryogenesis. We suggest that explanations for unequal frequencies of congenital phantoms for upper and lower as well as for left and right limbs (Table 2) may ultimately be found in the "laws" governing fetal development -such as the slightly earlier development of upper compared to lower limbs (O'Rahilly and Gardner 1975) and the differential vascularization of left and right limb buds (Bouwes Bavinck and Weaver 1986). With respect to this laterality issue, we note the surprisingly low interest by embryologists, teratologists and developmental neuroscientist in this issue and plead for a closer collaboration across the different medical and psychological disciplines.…”
Section: Phantoms Of Congenitally Absent Limbs As Manifestations Of Amentioning
confidence: 95%
“…Several of the experimental studies demonstrated that the initiating event in development of the limb and other malformations was an area of hemorrhage [Poswillo and Sopher, 1971;Poswillo, 1975;Kennedy and Persaud, 1977]. There followed a series of articles in the 1980s attributing a variety of birth defects, in addition to limb defects, to a presumptive vascular cause [Hoyme et al, 1981;Van Allen et al, 1982;Stevenson et al, 1986;Bavinck and Weaver, 1986].…”
Section: Review Of Prior Hypothesesmentioning
confidence: 99%
“…12,13 Pathogenesis No single etiological factor has been definitively associated with Moebius sequence, nor is it certain whether the pathology is a result of dysgenesis or degeneration. The most accepted theory proposes a disruption, in utero, of the basilar or vertebral arteries at a critical and early stage in gestation 14 by hypoxia, hyperthermia, infection, or drugs, in particular benzodiazepines, 15 alcohol and cocaine. 5 Misoprostol, a non-steriodal medication used for early non-surgical termination of pregnancies, has a strong association 16 and is thought to be responsible for a suggested recent increased incidence of Moebius sequence.…”
Section: Discussionmentioning
confidence: 99%